Methods in Bioengineering. - Zahn, Jeffrey D. (Methods in bioengineering., 2009)
This unique volume presents leading-edge microfluidics methods used to handle, manipulate, and analyze cells, particles, and biological components (e.g., proteins and DNA) for microdiagnostics. The authors offer clear and detailed guidance on microfabrication techniques utilized to create microfluidic devices and on-chip flow control and mixing Microsystems, protein and DNA handling devices for electrophoretic and isoelectric separations in microchromatography columns, microfluidic manipulations of droplets via electrowetting and particles via dielectrophoresis for separations and chemical rea.